The influence of differences between father and mother on adolescent adjustment - Jiménez-Iglesias, Antonia; Moreno, Carmen (Anales de Psicología / Annals of Psychology, 2014)
This paper analyzes how the differences between father and mother in affection, promotion of autonomy, disclosure, solicitation and knowledge influence on substance use (tobacco, alcohol and cannabis) and psychological well-being (health-related quality of life and life satisfaction). The sample was composed of 10170 boys and girls aged 13 to 18 years from two-parent families who participated in 2006 edition of Health Behaviour in School-aged Children (HBSC) study. Results indicated that adolescents whose both parents had high values for the different family dimensions used less substance and scored higher in psychological well-being. In contrast, the adjustment of adolescents whose both parents had low values for the different family dimensions was worse. Specifically, the most important dimension for substance use was parental knowledge and for psychological well-being was parental affection; adolescent disclosure was only relevant for alcohol use and quality of life, and parental promotion of autonomy for quality of life.